2004
DOI: 10.1055/s-2004-825726
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin mRNA Levels in Parametrial Adipose Tissue and Serum Adiponectin Levels are Reduced in Mice During Late Pregnancy

Abstract: Adiponectin, a fat-derived factor, is downregulated in insulin resistance and obesity; insulin resistance has been demonstrated during late pregnancy in both humans and in rodents. The present study examines the physiological change of adiponectin gene expression as well as the circulating levels of adiponectin during pregnancy. We examined the relative quantity of adiponectin mRNA produced in the adipose tissues of pregnant compared to virgin mice. We also measured serum adiponectin levels and parametrial adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
5
7
0
1
Order By: Relevance
“…The use of Gonal-F raised estradiol levels signifi cantly, and in line with previous reports on the effect of estradiol [10,11] , we observed a decrease in serum adiponectin levels from Day-basal to Day-hCG ( fi g. 1 ). It has been suggested that estradiol has a direct negative impact on serum adiponectin levels in vivo [11] .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The use of Gonal-F raised estradiol levels signifi cantly, and in line with previous reports on the effect of estradiol [10,11] , we observed a decrease in serum adiponectin levels from Day-basal to Day-hCG ( fi g. 1 ). It has been suggested that estradiol has a direct negative impact on serum adiponectin levels in vivo [11] .…”
Section: Discussionsupporting
confidence: 77%
“…The administration of insulin-sensitizing drugs signifi cantly increases serum adiponectin levels in insulin-resistant humans [9] . Adiponectin mRNA and serum adiponectin concentrations are signifi cantly reduced at pregnancy [10] . It has been suggested that estradiol has a direct negative impact on serum adiponectin levels in vivo [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Our longitudinal analysis in women from the pregravid state to the third trimester indicates that pregnancy in humans is a physiological situation in which circulating adiponectin is decreased, as is found in mice [11,27]. The 25% increase in fat mass from pregravid state to late pregnancy, together with the negative correlation between circulating adiponectin concentrations and fat mass, suggests that adipose tissue accretion is associated with signals for lowering adiponectin production or secretion even in the absence of obesity.…”
Section: Pregnancy Is a Situation Of Hypoadiponectinaemiasupporting
confidence: 56%
“…Consistent with these observations, only mice lacking iNOS, which showed a marked elevation in plasma high-molecular weight adiponectin levels, exhibited improved glucose tolerance and liver insulin action in response to rosiglitazone, confirming the high sensitivity of the liver to changes in highmolecular weight form concentrations (7). Adipose tissue remodeling caused by rosiglitazone treatment of iNOS knockout mice likely explains the raised plasma highmolecular weight adiponectin complexes in these animals because previous studies reported a strong inverse relationship between adipose cell size and adiponectin secretion (52,53).…”
Section: Discussionmentioning
confidence: 61%